Effect of redrawing of political boundaries on voting patterns: Evidence from state reorganization in India - Rajashri Chakrabarti; Joydeep Roy (Federal Reserve Bank of New York, 2007)
This paper analyzes the effect of a redrawing of political boundaries on voting patterns and investigates whether it leads to closer conformity of an electorate's voting patterns with its political preferences. We study these issues in the context of a reorganization of states in India. In 2000, Madhya Pradesh, the biggest state in India before the reorganization, was subdivided into Madhya Pradesh and Chhattisgarh, the latter accounting for less than one-fourth of the electorate of undivided Madhya Pradesh. Using socioeconomic composition and traditional voting patterns, we argue that there are differences in political preferences between Madhya Pradesh and Chhattisgarh. Next, in the context of a theoretical model that captures some of the basic features of the electoral scenario of the two regions, we predict that before reorganization, the smaller region would vote strategically to elect representatives with preferences more closely aligned to those of the bigger region. Once Chhattisgarh became a separate state, however, this motive would no longer operate, and the voting distributions of the two regions would differ. Using detailed data on state elections in Madhya Pradesh and Chhattisgarh in 1993, 1998, and 2003 as well as a difference-in-differences estimation strategy, we find that voting patterns in the two regions were indeed very similar before reorganization but strikingly different afterwards, with a relative shift in Chhattisgarh toward its inherent political preferences. These findings are reasonably robust in that they continue to hold after controlling for other confounding factors and survive several sensitivity tests.
Keywords: P16; D72; H77; O10; 330; political boundaries; voting; transfers; Gebietsreform; Teilstaat; Wahlverhalten; Indien